2022
DOI: 10.1021/acs.biomac.2c01241
|View full text |Cite
|
Sign up to set email alerts
|

Mapping 3D Printability of Ionically Cross-Linked Cellulose Nanocrystal Inks: Architecting from Nano- to Macroscale Structures

Abstract: Engineering the rheological properties of colloidal inks is one of the main challenges in achieving high-fidelity 3D printing. Herein, we provide a comprehensive study on the rheological behavior of inks based on cellulose nanocrystals (CNCs) in the presence of given salts to enable high-quality 3D printing. The rheological properties of the CNC suspensions are tailored by considering the nature of the electrolyte (i.e., 10 types of salts featuring different ion sizes, charge numbers, and inter-and intra-molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 62 publications
1
24
0
Order By: Relevance
“…CNC particles are placed closely together at this concentration. We have also carried out a comprehensive study on the optimization of CNC concentration in the presence of 10 different salts for high-fidelity 3D printing . According to these results, the highest G ′ and G ″ values can be achieved for CNC suspensions containing NaHCO 3 compared to other salts.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…CNC particles are placed closely together at this concentration. We have also carried out a comprehensive study on the optimization of CNC concentration in the presence of 10 different salts for high-fidelity 3D printing . According to these results, the highest G ′ and G ″ values can be achieved for CNC suspensions containing NaHCO 3 compared to other salts.…”
Section: Resultsmentioning
confidence: 97%
“…By plotting storage and loss moduli versus shear stress (stress amplitude test), the yield stress (τ y ), where both G ″ and G ′ are equal, could be estimated for all samples. The yield stress determined in this way is equivalent to the yield stress derived from a stress–strain curve …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[36][37][38] Intense shear-thinning behavior conjugated with high yield stress bestows inks with uid-like behavior during printing and a solid-like behavior immediately aer printing. 37,39 Recently, it has been shown that inks containing 7 wt% PEDOT:PSS possess proper rheological properties for high delity 3D printing of implantable conductive patches. 33 Further to that, it was shown that the addition of 2D MXenes nanosheets to PEDOT:PSS inks contributes to improving their rheological properties, leading to high-resolution printed lines.…”
Section: Introductionmentioning
confidence: 99%